The impact of using artificial intelligence applications in teaching - alalawi, Zainab suliman; Ramachandiran, Chandra Reka; Salam, Zailan Arabee Bin Abdul (Journal of Applied Technology and Innovation, 2021)
With the development of Artificial Intelligence (AI), the entire world, and the education field in particular, is facing great opportunities that can enhance and reform traditional education. This paper refers to the concept of artificial intelligence and the systems used in the field of education and many important aspects of applying artificial intelligence technology in this field, as it provides an overview of the history of artificial intelligence, its stages of development, its role in the future of education and its potential impact on learning, teaching and education. AI brings new opportunities for development as well as huge challenges for education. It has also been noted that issues related to ethical implications are rarely discussed in studies, such as critical reflection on educational and ethical implications as well as risks of implementing AI applications.